Pathways and challenges in the clinical translational of radiopharmaceuticals for pediatric investigations - Stauff, Erik; Karimi, Hanieh; Kecskemethy, Heidi H.; Shaffer, Thomas H.; Vali, Reza; Averill, Lauren W.; Yue, Xuyi (Frontiers in Medicine, 2025)
Radiopharmaceutical development and clinical translation face numerous scientific, ethical, and regulatory challenges, particularly within the pediatric population. Although molecular imaging holds significant promise for improving diagnosis and treatment across a spectrum of diseases, including pediatric-specific conditions like Kawasaki disease, autism spectrum disorders, attention-deficit/hyperactivity disorder, and neuroblastoma, the path from discovery to clinical application remains problematic. The U.S. Food and Drug Administration (FDA) provides three primary pathways—traditional Investigational New Drug (IND) applications, exploratory Investigational New Drug application (eIND), and the Radioactive Drug Research Committee (RDRC) mechanism—to facilitate clinical translation of radiotracers. However, these frameworks are not specifically tailored to pediatric needs. Children’s heightened sensitivity to ionizing radiation, coupled with physiological variability and ethical concerns, complicates trial design, dosimetry, and informed consent. Current practices also exhibit the limitation of inconsistent dosing standards across institutions. Emerging technologies—including improved single-photon emission computed tomography and positron emission tomography techniques, theranostics, whole-body scanners, and artificial intelligence-driven radiomics—offer potential to reduce these risks by enabling lower doses, reduced scan time, and more precise targeting. Nonetheless, a significant gap remains in translating these innovations into safe, equitable access for pediatric patients. Addressing these challenges requires updated regulatory guidance, ethical frameworks, and robust clinical strategies to ensure equitable access to molecular imaging innovations for children.